ACCOUNT OF THE FUNCTIONAL STATE INDICATORS OF MEN 40-60 YEARS OLD LEADING A SEDENTIAL LIFE DURING PHYSICAL AND RECREATION CLASSES WITH ELEMENTS OF MARTIAL ARTS - Huang, Peijun; Cherkashin, I.A.; Cherkashina, E.V.; Konovalov, I.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to take into account and evaluate the indicators of the functional state of men aged 40-60 years, leading a sedentary lifestyle, in the process of physical education and recreation classes with elements of martial arts. Methods and structure of the study. The method of cardiointervalometry was used to monitor the functional state. The experiment involved 60 men aged 40-60 years (48.07±6.22), who were divided into experimental (EG) and control (CG) groups of 30 people. The EG attended physical culture and health-improving classes with elements of martial arts. Representatives of the CG were engaged in a different program, the basis of which was running in an aerobic mode. Results and conclusions. At the end of the one-year experiment, significant differences were revealed in 13 out of 15 HRV parameters of men from the EG and one parameter of HRV in representatives of the CG (p<0.05; p<0.01). The analysis of intergroup differences in HRV indicators after the experiment showed that in men from the EG, compared with the representatives of the CG, 10 of the 15 studied parameters changed significantly. Special attention should be paid to such an indicator of HRV as the Stress Index (SI), which differs significantly between groups, the difference was 131.55% (p<0.01). The most pronounced changes affected the indicator of the activity of regulatory systems, the difference in the average parameters for the group was 155.7% (p<0.01). Thus, the positive effect of physical culture and health-improving activities with elements of martial arts on the cardiovascular system of men aged 40–60 years who lead a sedentary lifestyle was determined.